STABILITAS STATIS KAPAL POLE AND LINE KM ALDEIS DI PELABUHAN PERIKANAN AERTEMBAGA BITUNG SULAWESI UTARA - Pangalila, Fransisco PT (Sam Ratulangi University, 2011)
The uncertainty of ocean conditions, such as currents and waves, affects the maneuver ability and stability of vessel on the water. For this reason, a fishing vessel should fulfil specific prerequisites, such as strong vessel construction, good stability to extreme oceanic conditions, good maneuver ability, and thrust.Â â€œAldeisâ€ boat has a dimension of 15.50 m long, 2.80 m wide, and 1.10 m deep. Average ratio of those parameters was 5.50 for L/B, 13.05 for L/D and 2.37 for B/D, rspectively.Â The coefficient values of the boat shape were Cb = 0.54 for Cb, Cp = 0.73 for Cp, 0.74 for C and 0.79 for C3, respectively.Â The boat possessed a maximum shakes to 140 of the boat slant when the righting arm was at 0.20 m of the center point.